Bank liquidity, stock market participation, and economic growth - Mattana, Elena; Panetti, Ettore (Journal of Banking & Finance, 2014)
We develop a growth model with banks and markets to reconcile the observed decreasing trend in the relative liquidity of many financial systems around the world with the increasing household participation in direct market trades. At low levels of economic development, the presence of fixed entry costs prevents the agents from accessing the market, and pushes them towards the banks, which provide high relative liquidity. We characterize the threshold after which the agents are rich enough to access the market, where the relative liquidity is lower, and show that the relative liquidity of the whole financial system (banks and markets) drops because of the increasing market participation. We provide some evidence consistent with this theoretical prediction: a one-unit increase in an index of securities market liberalization leads to a drop in the relative liquidity of between 17 and 27 per cent.